The Effect of Brain Gym on the Learning Concentration of Student in STIKES NU Tuban - Basuki, Hyan Oktodia; Faizah, Hanim Nur (University of Muhammadiyah Malang, 2020)
Introduction: Concentration is an important aspect for a person in achieving learning and is related to the working ability of the brain. Maximum brain performance increases concentration, so that changes in parts of the brain also occur so there will be a decrease in the level of concentration. Objective: The purpose of this study is to compare the influence of the brain gym on student learning at STIKES NU Tuban. Method: The design of this study was Quasy Experimental by designing a pretest-posttest with a control group. The sample uses a systematic random sampling taken by 26 respondents (13 experimental group respondents and 13 control group respondents). Data collection using a questionnaire. Analysis using the Mann Whitney test. Results: Asymp results were obtained. Sig. = 0,000 which means the help of the composition of brain gym for the concentration of student learning. Discussion: Giving brain gym intervention as an ice breaker can make a good contribution to the concentration of student learning. Brain gym can be applied to students, just before the lesson starts or in the middle of the lesson, and the implementation time is approximately 10-15 minutes.